IMPROVING CREATIVE THINKING SKILLS THROUGH BEHAVIORAL RECONSTRUCTION THERAPY - Mangantes, Meisie Lenny (Guidance and Counseling Study Program, Pattimura University, 2021)
This paper was written with the aim to describe how counselors construct the behavior of counsellors who have symptoms of low learning motivation so as to increase theircreative thinkingskill. The technique to be used is true experiment with cognitive behavior counseling treatment approach for experimental group and interactive learning for control group. The use of cognitive behavior counseling aims to encourage counsellors in manipulating, managing and deforming information in their memory, so that counselors can easily form concepts, ways of reasoning and critical thinking, making decisions, in solving problems creatively. This research involves active counsellors who master the Techniques and approaches of behavioral cognitive counseling. The methods used in proving this research question will be discussed in the behavioral modification framework that the authors presented in 4 rounds of discussion. The first, the reduction and elimination of behavior; second, improved behavior through positive reinforcement and conditioned strengthening; third, create new behaviors through formation; Fourth, build behavioral resilience through strengthening schedules.